Factors Influencing Youth Decision-Making to Join Military Organizations in Indonesia - Toni; Haliansyah (Universitas Medan Area, 2025)
This article investigates the factors influencing young people's decisions to join military organizations in Indonesia, focusing on their motives, experiences, and the perceived Meaning of military service. To approach this problem, a theoretical reference is used to frame and explain the interplay of individual motives, lived experiences, and the perceived Meaning of military service in shaping enlistment decisions. The data is collected through structured surveys administered to young individuals who enlisted in military organizations during 2024 and analyzed quantitatively using Structural Equation Modeling (SEM) with second-order constructs to assess the relationships and hierarchies among the latent variables. This study concludes that motives, experiences, and perceived meaning significantly influence the decision-making process. Motive is the dominant factor, and ideals and economic dimensions best reflect the motive factor. This study provides valuable insights into the dynamics underlying military enlistment in Indonesia, offering implications for policy development, recruitment strategies, and understanding youth behavior in military contexts.